Pengembangan Sistem Pemesanan Tiket Konser Berbasis Web Untuk Meningkatkan Pengalaman Pengguna - Anang Habibi; Muhammad Ibnu Athoillah (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
In facing intense competition in the music event promoter industry, companies must always pay attention to changes in the environment, especially along with the rapid development of technology. The era of information technology has created new opportunities and challenges that companies must face in maintaining their competitiveness. One important aspect that needs to be considered is ordering tickets for music concert events online. This website offers a revolutionary solution by integrating innovative concepts through the use of HTML, JavaScript (JS), and CSS. The responsive and aesthetic interface ensures an efficient, engaging and interactive ticket booking experience for customers. By utilizing this technology, customers can easily and conveniently book tickets without having to leave the comfort of their home. More than just a ticket booking platform, this website also functions as a complete source of information about music events. This approach engages customers holistically, giving them access to up-to-date information, event schedules and other exclusive content. In this way, companies not only meet customers' transactional needs but also build deeper and more sustainable relationships. In the context of increasingly fierce competition, this innovative approach is expected to win the hearts of customers and make the company relevant amidst industrial dynamics. With a focus on a holistic user experience, this website aims to be more than just a ticket booking platform, but rather a premier destination for music lovers looking for information and a satisfying experience.